Interactive Multimedia Learning Design: Animation-Based Interactive Multimedia to Enhance Student Engagement and Understanding in Madrasah Ibtidaiyah - Bali, Muhammad Mushfi El Iq; Riandani, Rana (BASICA, 2026)
This study examines the use of animation-based interactive multimedia in classroom learning at Madrasah Ibtidaiyah and its contribution to students’ learning engagement and conceptual understanding. The research employed a qualitative case study design at MI Nurul Mun’im. The primary participants were 20 students who experienced classroom learning through animation-based interactive multimedia, while the classroom teacher served as a supporting informant. Data were collected through classroom observation, semi-structured interviews, and documentation, then analyzed through data condensation, data display, and conclusion drawing. The findings show four main patterns. First, the use of animation-based multimedia increased students’ interest in learning because lessons were perceived as more attractive and less monotonous. Second, it strengthened classroom engagement, as students became more active in asking questions, responding to the teacher, and participating in guided activities. Third, the media helped students understand lesson content more easily because visual movement, sound, and sequence made abstract material more concrete. Fourth, it supported early information literacy, especially in following visual instructions, recognizing symbols, and identifying simple digital information. The study concludes that animation-based interactive multimedia contributes to a more active, enjoyable, and student-centered learning environment in Madrasah Ibtidaiyah. Theoretically, the study reinforces the relevance of multimedia learning for Islamic primary education. In practice, it underscores the importance of teachers’ capacity to select and organize digital media appropriate to young learners’ developmental characteristics.